Microbial Manganese Reduction by Enrichment Cultures from Coastal Marine Sediments - Burdige, David J. (1985)
Manganese reduction was catalyzed by enrichment cultures of anaerobic bacteria obtained from coastal marine sediments. In the absence of oxygen, these enrichment cultures reduced manganates when grown on either lactate, succinate, or acetate in both sulfate-free and sulfate-containing artificial seawaters. Sodium azide as well as oxygen completely inhibited microbial manganese reduction by these enrichment cultures, whereas molybdate had no effect on them. The addition of nitrate to the medium slightly decreased the rate of Mn(2+) production by these enrichment cultures. These findings are consistent with the hypothesis that the manganese-reducing organisms in these enrichment cultures use manganates as terminal electron acceptors and couple manganese reduction in some way to the oxidation of organic matter.